FACTORS OF DEVELOPMENT OF SPEECH CULTURE IN CHILDREN OF YOUNG SCHOOL AGE (Universal International Scientific Journal, 2026)
This article highlights the main concept in the development of speech culture as the process of expressing thoughts, feelings and information in oral and written form. It highlights that the development of speech culture in primary school is an important factor in developing students' skills in expressing their thoughts correctly, fluently and logically. It explains that the development of speech culture is not limited to language teaching, but also develops a person's independent thinking, self-confidence and the ability to work in a team. It highlights that a student who is fluent and cultured in speech is active and successful not only in the classroom, but also in life.
Keywords: speech culture; linguodidactics; communicative competence